Walking the Old Road : A People's History of Chippewa City and the Grand Marais Anishinaabe - Drouillard, Staci Lola (Book collections on Project MUSE., 2019)
"Walking the Old Road revisits a time when generations of Ojibwe ancestors called the lost community of Chippewa City home. Staci Lola Drouillard, whose family once lived in Chippewa City, draws on memories, family history, historical analysis, and testimony passed down through generations to conduct us through the ages of early European contact, government land allotment, family relocation, and assimilation"--